A Study of Global Value Chain Through Islamic Economic Framework - Berampu, Lailan Tawila; Mulyono, Hardi (ExcelingTech, 2020)
Global Value Chain is a useful tool for tracking global production patterns for improving the economies of countries in the global economy with highly complex industrial interactions explicitly for poor and developing countries. This study seeks to link several previous studies, which discussed GVC with Islamic economic Fiqh. Of these, the objective of the current investigation is to study a GVC through Islamic economic framework (Fiqh). This study designed using Qualitative approach with reviewing the relevant literature (themes and topics). The results of this study found that the global dimension of GVC through the concept of Fiqh is input output, which consists of the sharia principles such as moral, quality and priority scale. Further, its distribution intended for Da'wah, education, social and economy. For geographical scope, it consists of a trade negotiation space of various countries. In conclusion, the structure of government in spending money to society who are weak in the faith will lead to deviation of economic activity from the right path. Keywords—Global value chain, Islamic economic framework, Concept of Fiqh, Input-Output